Laparoscopic versus open ventral hernia repair - Alsadiqi, Rayan; Albishri, Abdullah; Almaghrabi, Ahmad; Aljedaani, Badr; Alghamdi, Khalid; Alhijab, Fatimah; Alsulami, Mohammed; Hussain, Abdullah; Alshaikh, Mohammad; Jaad, Nafisah (International Journal Of Community Medicine And Public Health, 2018)
From the patient’s perspective, a ventral hernia can cause pain, adversely affect function, increase size, cosmetically distort the abdomen, and incarcerate/strangulate abdominal contents. The only known cure for a ventral hernia is surgical repair. The purpose of the current analysis was to review the published randomized controlled trials (RCTs) of the surgical care of ventral hernia. We conducted this meta-analysis using a comprehensive search of EMBASE, MEDLINE, PubMed, Cochrane Database of Systematic Reviews, and Cochrane Central Register of Controlled Trials till 01 March 2018 for randomized controlled trials on the use of mesh reinforcement in abdominal wall hernia repair. 15 studies met the search criteria, laparoscopic repair (OR 0.59; 95% CI 0.02–6.71) had the highest probability of having the lowest rate of surgical site infection. Among open mesh repair techniques, sublay repair (OR 1.41; 95% CI 0.01–5.99) had the highest probability of being the best treatment. Among patients experiencing ventral hernia repair, mesh reinforcement ought to be used regularly when there is no infection. Sublay mesh might outcome in fewer reappearances and surgical site infections. The quality of evidence to support these recommendations is moderate to high.